The Slovene Countryside in Transition from Traditional to Market-Oriented Agriculture - Klemenčič, Vladimir; Klemenčič, Matjaž (Journal for Geography, 2009)
In the following paper the contemporary problems of the Slovene countryside will be discussed with special emphasis on the problems of image of the cultural landscape, which developed as a consequence of the rapid economic development of Slovenia. The relationship among different individual land categories is changing fast and the remnants of the economic structure of classic agrarian and modern industrial society are intertwined in contemporary Slovenia. We will deal especially with the consequences of European market-oriented agrarian policy, which is applied towards large differences between individual regions of Slovenia.
Keywords: farmland usage; harmonious development of cultural landscape; EU; Slovenia